An Evidence-Based Possible Framework for Addressing Economic and Health Challenges of the Ageing Population in Bangladesh - Mohammad Mastak Al Amin (European Scientific Journal, ESJ, 2019)
Political unrest, poor economic growth, low savings and tiny coverage of pension are making the elderly to face challenges to survive in Bangladesh. Health care costs of elderly affected their household living standard significantly due to the unbalanced financial liability in Bangladesh. In this study, we conducted a survey on elderly of 311 sample size from four thana: Dhanmondi, Gulshan, Uttara and Mohammadpur in Dhaka City. Both probability and non-probability sampling methods were used to collect demographic, economic, and health related information of elderly. Elderly mostly depend on their family and pension for their financial support at their retirement age, while they rarely depend on insurance in Bangladesh. Besides, price inflation is another cost driver for elderly. This paper focuses on exploring the current state of health and economic position of elderly. Therefore, the logistic regression model was derived to identify the significant key factors (income, pension, health Insurance, physical independence & gender) which were influencing the treatment cost of elderly. Hence, our study also suggests the policy implications (such as specialized bank, social insurance authority, security alert apps, subsidies catering companies, specialized pharmacies etc.) for the upcoming ageing challenges in Bangladesh.